Societal dangers of migrant crisis narratives with a special focus on Belarussian and Ukrainian borders with Poland - Grabowska, Izabela (Frontiers in Sociology, 2023)
This paper presents societal dangers of migrant crises narratives. Society in the 21st century has experienced a variety of crises, from the fiscal crisis and the migration crisis to the pandemic and the inflation crisis. We formulated a number of societal dangers related to the migrant crisis narrative, which are not sharp and exclusive but invite further consideration: (1) Societal fatigue, which relates to a rapid change in societal moods, usually from a positive to a negative attitude towards migrants, but above all this danger is connected with an aid burnout in a civil society; (2) Othering, which includes normativity, the labelling of migrants, double or multiple standards in the treatment of migrants and refugees from various origins; the societal danger of othering contributes to societal divisions, polarizations, tensions and conflicts based on ethnicity, religion, race and gender; (3) Political functionality, whereby migration as a political construct serves as a “whipping boy” for politicians to divert public opinion from recurrent problems; it also involves the creation of piecemeal, reactionary, ad hoc public policies, and the overuse of a protocol of a state of emergency in order to bring about a centralization of political power. This paper forms part of the Horizon 2020 Project X with an expert stakeholder study from seven European countries: Germany, Italy, Poland, Romania, Luxembourg, Sweden and the UK. It takes also into account contextual international and national public opinion surveys.